Penyuluhan penyakit IMS pada Karyawan Karaoke di Tempat Karaoke Kota Langgur dan Kabupaten Maluku Tenggara - Amanda Gracia Manuputty; Alessandra Saija; Laura Bianca Sylvia Huwae; Sean Istia; Fitri Kadarsih Bandjar; Aldo Evan Wijaya; Iqbal Alaudilah Harahap; Dewi Najira Kabakoran (I-Com: Indonesian Community Journal, 2024)
ABSTRACT Sexually transmitted infections (STIs) have a significant influence on sexual and reproductive health on a global scale. The occurrence of STIs surpasses 1 million cases daily, highlighting the widespread impact of these infections. The repercussions of STIs can extend beyond the immediate impact of the infections themselves, that may lead to serious consequences. In the South East Asia Region morbidity and mortality from sexually transmitted infections (STIs) is significant, should increase concern about sexual, reproductive health of women, newborn and child health. Highlighting the current situation, it is necessary to take immediate steps to reposition STIs control as a public health priority. The community service method consists of pre-test, education, and post-test. The community service carried out in the localization of Langgur City, Southeast Maluku Regency had a positive impact with an increase in knowledge in participants who participated in activities regarding sexually transmitted infections. Overall knowledge of sexually transmitted infections and HIV/AIDS among prostitute is quite good, seen from the increase in post-test results. In addition, participants who are positively infected with sexually transmitted diseases are expected to be treated according to applicable operational standards. Keywords: community service; sexually transmitted infections; prostitute